Effect of physical activity on asthma control in schoolchildren - dos Santos, Ana Paula (Einstein (Sao Paulo), 2019)
OBJECTIVE: To investigate the effect of levels of physical activity on asthma control in children. METHODS: A cross-sectional study, including public school students aged 8 to 12 years, of both sexes, with asthma, from a capital and a medium-sized cities in Southern Brazil. At home, the students answered the questionnaire on levels of physical activity and disease control. RESULTS: A total of 482 schoolchildren with asthma participated in the study, with mean age of 10.9±2.2 years, and 253 (52%) were girls. Regarding disease control, 50% had controlled asthma, and 67% were considered sedentary. Schoolchildren with controlled asthma were more active than those with uncontrolled asthma (p=0.032). Active schoolchildren were more likely to have asthma controlled (OR=1.5; 95%CI: 1.04-2.25). CONCLUSION: The results demonstrated an association between physical activity levels and asthma control. More active schoolchildren were more likely to have asthma controlled.